Implementation of a program for treatment of acute infections in nursing homes without hospital transfer - Kagansky, Nadya; Rosenberg, Reena; Derazne, Estela; Mazurez, Evelina; Levy, Yochai; Barchana, Micha (Frontiers in Medicine, 2024)
Background Nursing care residents have high hospitalization rates. To address this, we established a unique virtual geriatric unit that has developed a program aimed at providing support to nursing homes. Aims We aimed to evaluate effectiveness of in-house intravenous antibiotic treatment in nursing hospitals after the implementation of the specially designed training program. Methods A cohort study of nursing home residents to evaluate a training program for providers, designed to increase awareness and give practical tools for in-house treatment of acute infections. Data obtained included types of infections, antibiotics used, hospital transfer, and length of treatment. Primary outcomes were in-house recovery, hospitalization and mortality. Univariate analysis and multivariable logistic regression analysis to assess association between different factors and recovery. Results A total of 890 cases of acute infections were treated with intravenous antibiotics across 10 nursing homes over a total of 4,436 days. Of these cases, 34.8% were aged 90 years or older. Acute pneumonia was the most prevalent infection accounted for 354 cases (40.6%), followed by urinary tract infections (35.7%), and fever of presumed bacterial infection (17.1%). The mean duration of intravenous antibiotic treatment was 5.09 ± 3.86 days. Of the total cases, 800 (91.8%) recovered, 62 (7.1%) required hospitalization and nine (1.0%) resulted in mortality. There was no significant difference observed in recovery rates across different types of infections. Discussion Appling a simple yet unique intervention program has led to more “in-house” residents receiving treatment, with positive clinical results. Conclusion Treating in-house nursing home residents with acute infections resulted in high recovery rates. Special education programs and collaboration between healthcare organizations can improve treatment outcomes and decrease the burden on the healthcare system.